PERLINDUNGAN HUKUM BAGI NOTARIS AKIBAT PEMALSUAN SALINAN AKTA NOTARIS YANG DILAKUKAN OLEH PIHAK LAIN YANG BUKAN PENGHADAP - Asty Lestari Pratama Putri; Putra Hutomo; Hedwig Adianto Mau (Journal of Innovation Research and Knowledge, 2025)
Notaries as public officials are authorized to assist the goverment in terms of making an authentic deeds. Each notaries responsible for every deeds that been made, either in the form fo minutes of deeds or copies of notarial deeds. In carrying the duties as notaries, they have rights to be under protection of law from goverment and related organization. Research problems in this study are to see what are legal concequences of forged copies of notarial deeds by other parties who are not the parties? And what are the legal protection for notaries against forged copies of notarial deeds by other parties who are not the parties? This study, using theory of protection law by Satjipto Rahardjo and theory of legal consequences by Soeroso. Method in this study uses Types of Normative Juridical Research that is a literature legal research or secondary data with primary, secondary, tertiary legal material resource. As for the approach of this study uses Legislative Approach, Conceptual Approach, Analytical Approach, and Case Approach. And collection of the legal material done by identifies and inventories positive rule of law, literature, journal, and other legal material. As for analysis technique for legal material done by Grammatical law interpretation and analogical law construction method. The result of this study shows that consequences of legal for forged copies of notarial deeds by other parties who are not parties are, the notarial deeds still bind for every parties and is a protection for notaries. Things that can be done by notaries are to include an exoneration clause in the contents of the notarial deeds to mitigate problem in the future. It is suggested that notaries could be more cautious in publishing copy of deeds and keeps digitalized copy of deeds to avoid forgery.